Why foodborne botulism cannot be caused by honey. (October 2022) - Dorner, Martin B.
Highlights: Response letter to the paper by Goin et al. Anaerobe Volume 75, 2022: 102578. Goin et al. suggests honey a cause for foodborne botulism. Response explains why foodborne botulism cannot be caused by honey. Botulism as results of intestinal colonization is discussed.